THE PHILOSOPHY AND THE MARKET: BETWEEN HOMO FABER AND HOMO SAPIENS - Souza, Guilherme Alberti de (Seven Editora, 2025)
Since Antiquity, social life has established a hierarchy between vita activa and vita contemplativa. This hierarchy gave rise to the concepts of homo faber and homo sapiens. Beginning in modernity, with the scientific revolution, homo faber rose to the top of the hierarchy, assuming various characteristics as the centuries progressed. However, it is in contemporaneity that this split becomes radical, and the market poses the question: What is Philosophy for? Thus, the culture industry promotes a new mode of Dasein: an ontology of voluntary servitude. In light of this, the present article intends to serve as a response to those who seek to instrumentalize the human condition. DOI: https://doi.org/10.56238/sevened2025.036-062